2016
DOI: 10.1093/jme/tjw218
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence ofAmblyomma americanum(Acari: Ixodidae) and Human Infection WithEhrlichia chaffeensisin Wisconsin, 2008–2015

Abstract: Because of the increasing incidence of human ehrlichiosis in Wisconsin, we assessed reports of human infections by Ehrlichia chaffeensis and the distribution of its vector, the lone star tick (Amblyomma americanum (L.)). From 2008 through 2015, 158 probable and confirmed human cases of E. chaffeensis infections were reported to the Wisconsin Department of Health Services. Five cases without travel history outside of Wisconsin were confirmed as E. chaffeensis by polymerase chain reaction. Surveillance for the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Updated distribution maps for this species that included SWAT results were reported in Eisen et al [15] and we found no additions for the additional 2016–2017 collections included herein. Similarly, A. americanum records have been recently summarized [17] and no additions were identified. D. variabilis was widely distributed as it was submitted by 32 of the 35 participating counties (no specimens from La Crosse, Vernon, or Marathon Counties) with reports for eight additional nonparticipant counties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Updated distribution maps for this species that included SWAT results were reported in Eisen et al [15] and we found no additions for the additional 2016–2017 collections included herein. Similarly, A. americanum records have been recently summarized [17] and no additions were identified. D. variabilis was widely distributed as it was submitted by 32 of the 35 participating counties (no specimens from La Crosse, Vernon, or Marathon Counties) with reports for eight additional nonparticipant counties.…”
Section: Resultsmentioning
confidence: 99%
“…These studies demonstrated that I. scapularis has undergone a dramatic range expansion in Wisconsin since the 1980s [15]. Another vector species, Amblyomma americanum Linnaeus, formerly unknown in Wisconsin, has also been detected with increasing frequency [16,17]. Our current understanding of the presence and geographical range of other ixodid tick species in Wisconsin comes from studies that summarize the results of collections from animals or humans that largely occurred between the early 1900s and the 1970s ([3,6,18,19,20,21,22,23,24,25,26,27,28,29] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to I. scapularis, Amblyomma americanum (the lone star tick) populations are emerging in the state. This tick is responsible for the transmission of Ehrlichia chaffeensis [18].…”
Section: Introductionmentioning
confidence: 99%
“…americanum have been spreading northwards in Illinois (Gilliam et al 2020, Lyons et al 2021, Indiana (Wojan et al 2021), and Ohio (Fitak et al 2014). Although there have been increases in A. americanum detected by the public in Wisconsin (Christenson et al 2017) and southern Ontario (Nelder et al 2019), established populations have not yet been declared in those areas (at the time of manuscript submission).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, breeding populations of A. americanum have been documented in southern New England (Stafford et al 2018, Telford et al 2019) and in states surrounding the Great Lakes, established populations of have been spreading northwards in Illinois (Gilliam et al 2020, Lyons et al 2021), Indiana (Wojan et al 2021), and Ohio (Fitak et al 2014). Although there have been increases in A. americanum detected by the public in Wisconsin (Christenson et al 2017) and southern Ontario (Nelder et al 2019), established populations have not yet been declared in those areas (at the time of manuscript submission). As of July 2019, the Minnesota Department of Public Health has not reported any established populations of A. americanum although they have been reported by residents since 1998 (https://www.health.state.mn.us/diseases/tickborne/longstarstickreportsmap.pdf, accessed 10/6/21), and established populations have been identified in nearby counties to the west in South Dakota (Black et al 2021) and to the south in Iowa (Springer et al 2014).…”
Section: Introductionmentioning
confidence: 99%